Complementary and alternative medicine in the technology age. - Kern, S.E.
The impact of complementary and alternative medical therapies as potential low-cost solutions to healthcare problems is explored. This issue is presented to stimulate and challenge the bioengineering community to consider the opportunities present in these low-cost healthcare solutions, which can be disseminated easily without borders imposed by economic status and resource availability. This area of research provides opportunities to develop global solutions to significant healthcare problems and presents interesting adventures in understanding human physiology and pathophysiology response.
Keywords: Alternative medicine; Bioengineering; Complementary medicine; Human physiology; Low-cost healthcare solutions; Medical therapies; Pathophysiology response; Technology age